Studi Tentang Jaringan Sosial Budaya, Ekonomi dan Politik Diaspora Suku Bugis di Penajam Paser Utara, 2002-2024 - Amiruddin Amiruddin; Muhammad Rasyid Ridha; Ahmadin Ahmadin (Jayapangus Press, 2026)
This study examines the dynamics of the Bugis diaspora in Penajam Paser Utara Regency from 2002 to 2024, focusing on the formation and roles of social, cultural, economic, and political networks within the region. The migration of the Bugis ethnic group to Penajam Paser Utara has been driven by economic factors, the openness of coastal areas, and strong kinship networks connecting origin and destination regions. This research is motivated by the author’s interest in understanding the socio-economic, political, and cultural networks established by the Bugis diaspora. The study aims to analyze the role of these networks in shaping the economic, political, and socio-cultural life of the Bugis community in Penajam Paser Utara. A descriptive qualitative approach was employed, with data collected through interviews, observations, literature review, and documentation. The findings reveal that the Bugis diaspora has successfully developed strong social networks based on kinship and religious values, which serve as a fundamental foundation for cultural adaptation and local economic development, particularly in the fisheries, trade, and maritime transportation sectors. In the political sphere, the Bugis community actively participates in local governance structures and has become one of the influential ethnic groups in regional political dynamics. The integration of Bugis cultural values with the local social context has produced a distinctive diaspora identity adaptive and open to change, yet firmly maintaining ethnic solidarity and the values of siri’ na pacce as guiding principles of life. In conclusion, the Bugis diaspora in Penajam Paser Utara represents a significant example of how migrant communities build resilient socio-cultural and economic networks in new environments, contributing substantially to sustainable community development.